Influence of Slow-Release Fertilisers on Growth of Rubber (Hevea Brasiliensis) Seedlings - Tong, Viet Thinh (1997)
Rubber, Hevea brasiliensis, is a valuable crop of some countries in Asia. In the rubber industry, fertiliser application is one of the most effective methods to enhance growth of rubber seedlings in the nursery. However, application of chemical fertilisers has several disadvantages such as fast nutrient leaching, fertiliser bum and requirement of intensive labour for split applications. In recent years, slow-release fertilisers have been introduced to solve the above problem so n many crops including rubber. Studies on the effect of slow-release fertilisers on rubber are limited and there has been no work reported on the use of isotope technique to accurately study nutrient uptake and efficiency of fertilisers use. This study was set up with the aim of studying the rate of nutrient release of slow-release fertilisers and their effect on the performance of rubber seedlings using 15N isotope dilution technique. Two experiments, namely, laboratory incubation and glass-house experiments were conducted. Five fertilisers were evaluated, four of which were slow-release fertilisers (Agroblen, Best Tab, Kokei Nugget and Nurseryace) and one conventional chemical fertiliser (Nitrophoska Yellow). In the soil-incubation experiment, Bungor and Sungai Buloh series soils were used, while in the glass-house experiment, only Bungor series soil was used Results from the incubation experiment showed that during the period of incubation, Nitrophoska Yellow gave the fastest rate of fertiliser decomposition and NPK release, while Nurseryace were persistently the lowest. Higher fertiliser decomposition and release of N and K were obtained in Bungor series soil as compared to Sungai Buloh series soil. However phosphorus release in Bungor series soil was lower than that in Sungai Buloh series soil. It was found that there was a very close relationship between fertiliser decomposition and NPK release of slow-release fertilisers, particularly for Kokei Nugget and Nitrophoska Yellow.